1997
DOI: 10.1016/s0029-7844(97)00113-0
|View full text |Cite
|
Sign up to set email alerts
|

Labor induction with intravaginal misoprostol in term premature rupture of membranes: A randomized study

Abstract: Intravaginal administration of misoprostol induces labor safely and effectively in patients with PROM at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 11 publications
3
31
0
1
Order By: Relevance
“…In 1996, Ngai et al [47] investigated the effectiveness of oral misoprostol as a cervical-priming agent for patients presenting with prelabor rupture of membranes at term and suggested that oral misoprostol is an effective agent for this group of patients. Similar results were published by Sanchez-Ramos et al [27] in 1997 and Shetty et al [48] in 2002. The latter concluded that active management with oral misoprostol resulted in more women going into labor and delivering within 24 h of prelabor rupture of membranes with no increase in maternal or neonatal complications.…”
Section: Labor Induction At Termsupporting
confidence: 88%
See 1 more Smart Citation
“…In 1996, Ngai et al [47] investigated the effectiveness of oral misoprostol as a cervical-priming agent for patients presenting with prelabor rupture of membranes at term and suggested that oral misoprostol is an effective agent for this group of patients. Similar results were published by Sanchez-Ramos et al [27] in 1997 and Shetty et al [48] in 2002. The latter concluded that active management with oral misoprostol resulted in more women going into labor and delivering within 24 h of prelabor rupture of membranes with no increase in maternal or neonatal complications.…”
Section: Labor Induction At Termsupporting
confidence: 88%
“…With these promising results, the use of misoprostol became an area of active research in the following decade. Many studies, including several systematic reviews and metaanalysis of published randomized trials [25][26][27][28][29][30], have shown misoprostol to be more effective than a placebo or other prostaglandins for the induction of labor. Misoprostol can achieve a higher rate of vaginal delivery within 24 h, a shorter induction-to-delivery interval, and significantly lower overall cesarean section rates than pooled figures for the control groups [31].…”
Section: Labor Induction At Termmentioning
confidence: 99%
“…The present study was compared specifically with studies done by Ralph et al, 5 Luis et al, 6,7 Adair et al, 8 Butt et al, 9 Suk et al 10 …”
Section: Sir Alec Turnbull (1976)mentioning
confidence: 95%
“…For induction of labor at term, clinical trials have compared misoprostol with placebo, 68,69 oxytocin, [70][71][72] and other prostaglandins, primarily dinoprostone (prostaglandin E 2 ) gel [73][74][75][76][77][78][79] or the dinoprostone vaginal insert. 80,81 These studies included most indications for which labor is induced, including premature rupture of membranes.…”
Section: Induction Of Labor With a Viable Fetusmentioning
confidence: 99%